(untitled) (Malaysian Journal of Fundamental and Applied Sciences, 2017)
Flavor and aroma cannot be separated in food industries. The manipulation of the ingredients to increase the taste has started since early civilization. Common example of the earliest application of ingredients to increase the savory taste of the food is soy sauce production. The process of digging out the aroma and flavor includes frying, stewing, grilling as well as fermenting. Nowadays, much complex savory system in food can be achieved through several processes such as Maillard reaction and protein hydrolysate production. The food produced will not only be tasty but healthy. This concept was first focusing on human food production. However, the increasing number of pet owner for about 10% annually since 2008 as reported by US Pet Owner Society demands the same concept to be implemented in pet food industries. Since most pet owners considered their pets as part of their family, the pet food source from 4D (dead, dying, disable and diseased) animals are unacceptable. Therefore, the pet food industries are competing with human food industries to get the clean source of meat for food as well for flavor production. An alternative to overcome this is by utilizing the viscera of the slaughtered chicken for palatant or flavor production. Aside from meat, bones and feathers, viscera are also abundantly being considered as waste and were not fully utilized. They are rich in protein. The protein can be recovered using suitable process and later turned into a value-added product such as flavor. There is a study available for converting the protein waste into protein hydrolysate via chemical and physical technique. However, only few reports are available for the conversion process via indigenous microbes and enzymes. It is believed that the indigenous microbes and enzymes (protease, peptinase) can be utilized for protein hydrolysate production which will later can be utilized as palatant. The palatant produced should have Sulphur-based aroma compound such as 2-methyl-3-furanthiol and 2-furfuryl-thiol which serve as precursors for chicken aroma.